Effectiveness of Hot Water Foot Bath on The Quality of Sleep Among Elderly Patients - Kumbhar, Udaykumar; Pawar, Ajit; Shinde, Mahadeo B; Ombale, Sneha; Hulwan, Dhanshri (International Journal of Psychosocial Rehabilitation, 2020)
Introduction-Common problem in the general population is poor sleep quality; it is due to lifestyle changes and work-related demands. With aging sleep problems increase sharply. Physical, mental, and social aspects of well-being are affecting due to Poor sleep quality. Objectives: Assessment and comparison of quality of sleep among hospitalized elderly patient before and after hot water foot bath .Methods: Comparative study was conducted with evaluative approach on 50 elderly patients which was selected by non probability convenient sampling method and was divided in experimental and control group (25 in each group). Quality of sleep was assessed by Pittsburgh Sleep Quality Index (PSQI) before and after hot water foot bath in experimental group and in control group before and after routine nursing intervention. Results: Control group pre-test mean was 8.64 (2.307) and post-test mean was 10.92 (2.857), mean difference was -2.280, ‘p’ value after pre-test and post-test comparison was 0.0010 where as in experiment group pre-test mean was 10.96 (1.791) and post-test mean was 3.92 (1.187), mean difference was 7.040, ‘p’ value after pre-test and post-test comparison was 0.0001 which indicate that hot water footbath is more effective than routine nursing care to improve quality of sleep. Conclusion: Based on the findings of the result of the study show that hot water foot bath among elderly patients is more effective than routing nursing care. Especially it improves quality of sleep.